2020
DOI: 10.1093/jas/skaa255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a decision support system for precision feeding of gestating sows

Abstract: Precision feeding (PF) with the daily mixing of two diets with different lysine content (high (H) or low (L)) was previously reported for growing pigs to reduce protein intake and N excretion compared to a conventional feeding (CF) based on a single diet (C). Using a simulation approach based on farm data, the objective of the present paper was to describe and evaluate a decision support system (DSS) for the PF of gestating sows allowing the daily distribution of a tailored ration to each sow. Two datasets, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Indeed, the estimated amount of excess N was not different between the PF and CON feeding programs in pregnancy 1, but in pregnancies 2 and 3, excess N was reduced for the sows that received the PF program. This supports the work of others which demonstrated that phase- or precision-feeding gestating sows can reduce both nitrogen intake and excretion, without negatively affecting sow performance ( Clowes et al, 2003a ; Gaillard et al, 2020 ). In addition, in the current study, excess P was greater for sows that received the PF vs. CON program, despite similar retention efficiencies that were comparable to those reported by others (e.g., van der Peet-Schwering et al, 1999 ; Buis, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the estimated amount of excess N was not different between the PF and CON feeding programs in pregnancy 1, but in pregnancies 2 and 3, excess N was reduced for the sows that received the PF program. This supports the work of others which demonstrated that phase- or precision-feeding gestating sows can reduce both nitrogen intake and excretion, without negatively affecting sow performance ( Clowes et al, 2003a ; Gaillard et al, 2020 ). In addition, in the current study, excess P was greater for sows that received the PF vs. CON program, despite similar retention efficiencies that were comparable to those reported by others (e.g., van der Peet-Schwering et al, 1999 ; Buis, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…The LP and HP diets contained the same P contents and since the PF program provided a greater feed allowance to sows, P intake and excretion were also greater. If P was provided more precisely (i.e., scaled with Lys in the HP and LP diets or by including a third diet to the blend), then there is also further opportunity to reduce feed costs as well as P excretion to the environment ( Gaillard et al, 2020 ). Finally, the cost of the PF program will also be largely influenced by commodity prices and ingredient selection.…”
Section: Discussionmentioning
confidence: 99%
“…These values may be compared to the 38% reduction in N and P excretion found in growing pigs ( Pomar et al, 2011 ). For a similar approach in gestating sows, Gaillard et al (2020) found a reduction in N and P excretion of 16.7% and 15.4%, respectively. The present study also reports an 11.7% reduction in feeding cost, which could confirm the economic benefits of precision feeding strategies reported for growing pigs (10.5%, Pomar et al, 2011 ) and gestating sows (3.6%, Gaillard et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…It was assumed that the current practise of blending high-nutrient and low-nutrient basal feeds would be largely compatible with such adjustments, although this is not fully guaranteed. To ensure universality, blending three basal feeds is likely to be needed ( 90 ).…”
Section: Discussionmentioning
confidence: 99%